1,2-Dihydroxy-2-(3-methylbut-2-enyl)-3-oxo-2,3-dihydro-1H-indene-1-carboxylic acid monohydrate - Acácio Ivo Franscisco; Gleiciani de Q. Silveira; Jackson A. L. C. Resende; Tatiane L. Balliano; Valéria R. S. Malta; Antonio Ventura Pinto (Acta Crystallographica Section E, 2010)
The title compound, C15H16O5·H2O, is an intermediate of the Hooker oxidation reaction, used for the synthesis of 2-hydroxy-3-(2-methylprop-1-enyl)naphthalene-1,4-dione (nor-lapachol). The packing in the crystal structure is arranged by an O—H...O hydrogen-bonded network along the [100] and [010] directions. Each organic molecule is linked to four other molecules via the hydroxy groups. The water solvent molecule is connected to carboxylic acid groups by three hydrogen bonds.